2023
DOI: 10.1002/cam4.6078
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‐100‐5p in cancer‐associated fibroblast‐derived exosomes facilitates lymphangiogenesis in esophageal squamous cell carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…In addition, OCSCC cells co-cultured with CAF-EVs tended to form larger tumors in the xenograft-bearing mice and increased lymph node metastases in mice induced with an orthotopic xenograft model. The most recent report also suggested that a large number of CAFs were present in esophageal squamous cell carcinoma, leading to a poor prognosis, and CAF-derived EVs enhanced lymphangiogenesis in xenografts formed by esophageal SCC cells [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OCSCC cells co-cultured with CAF-EVs tended to form larger tumors in the xenograft-bearing mice and increased lymph node metastases in mice induced with an orthotopic xenograft model. The most recent report also suggested that a large number of CAFs were present in esophageal squamous cell carcinoma, leading to a poor prognosis, and CAF-derived EVs enhanced lymphangiogenesis in xenografts formed by esophageal SCC cells [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic metastasis is another important method of tumor metastasis besides hematogenous metastasis. The reduction of CAF-derived exosomal miR-100-5p in esophageal squamous cell carcinoma (ESCC) may promote the growth, migration, and invasion of tumor-related lymphatic endothelial cells by increasing the expression of IGF1R/PI3K/AKT, ultimately leading to the development of lymphatic vessels ( Chen et al, 2023 ) ( Figure 2 ).…”
Section: Function Of Caf-derived Exosomal Mirna In Promoting Tumorige...mentioning
confidence: 99%
“…demonstrated that CAFs-derived exosomes might accelerate cell proliferation and regulate apoptosis by RIG-I/IFN-b signaling and influence the chemosensitivity of ESCC to DDP, and that targeted inhibition of the RIG-I/IFN-b signaling axis in the exosomes of CAFs maybe an underlying therapeutic tactics for ESCC. Furthermore, the presence of CAFs and micro-lymphatic vessels in ESCC was associated with a poor prognosis (176). Exosomes derived from CAFs promote invasion, proliferation, migration, and tube formation of tumor-associated lymphatic endothelial cells (TLECs), while miR-100-5p exerts the opposite effect.…”
Section: Crosstalk Between Escc Cells and Cafsmentioning
confidence: 99%